Moving Toward Climate-Resilient Transport : The World Bank’s Experience from Building Adaptation into Programs - Ebinger, Jane Olga; Vandycke, Nancy (World Bank, Washington, DC, 2016)
Infrastructure and services are critical to development and form the backbone of economic and community activities at the local, regional, national, and international levels. They enable the distribution of goods and services within and between countries and ease access to schools, markets, and health services. Food security and vaccination programs, for example, require functioning roads and railways and access to ports and airports to move critical supplies to people. While there is agreement on the need for greater connectivity, there is much debate on how to deliver it given the challenges from climate change. The contribution of the transport sector to increasing greenhouse gas emissions (GHG) and fossil fuel consumption have been at the center of global discussions on climate change. Transport is among the fastest growing sectors for CO2 emissions from fuel combustion, and it is estimated to contribute approximately 23 percent of total energy-related CO2 emissions in 2010. Transport enables development, but causes traffic congestion, pollution, noise, and road accidents, that together bring about 2 percent to 10 percent reduction in country-level GDP. Reversing this trend in emissions growth will require action to decouple emissions growth from GDP growth, driven by passenger and freight activity. This includes policies to encourage investment in low-carbon transport modes; programs to curb energy and emissions growth; and action to transform the way countries manage transport services.